Wahbah al-Zuhaili's interpretation of the Qur'anic Verses that hint at nepotism in al-Tafsir al-Munir fi al-'Aqida wa al-Shari'ah wa al-Manhaj - Basyiruddin, Muhammad Hafizh; Yunus, Badruzzaman M. (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This research discusses how Wahbah al-Zuhaili interprets verses that hint at nepotism in Al-Tafsir al-Munir fi al-'Aqida wa al-Syari'ah wa al-Manhaj. The verses discussed in this research are based on terms that are the principle of nepotism in the Qur'an such as al-Khiyanah, al-Ghill, Syafa'ah sayyi'ah, ittiba' al-Hawa, and ja'l wazir min Ahl. This research uses a qualitative method with a literature study approach to conceptually examine various matters related to nepotism from the perspective of the Qur'an. Therefore, this research is a type of qualitative and thematic research through literature review, namely by writing, reducing, presenting data, and analyzing it. The purpose of this research is to find out how the interpretation of Wahbah al-Zuhaili in Al-Tafsir al-Munir fi al-'Aqidah wa al-Syari'ah wa al-Manhaj regarding verses that hint at nepotism. The results of this research show that Wahbah al-Zuhaili views nepotism proportionally by distinguishing between negative and positive. Negative nepotism occurs if the position is given only because of proximity, without regard to qualifications, so it includes betrayal, ghulul, and intercessory sayyi'ah, ittiba' al-Hawa, and ja'l wazir min Ahl. On the other hand, nepotism is allowed if it is based on competence, honesty, good intentions, and does not violate the Sharia. Harun's appointment by Musa is an example of legitimate nepotism because it is based on preaching motivation and qualifications. For al-Zuhaili, justice, qualification, and intention are the main yardsticks in evaluating nepotism.